Formulating and improving care while mitigating risk in a military Ebola virus disease treatment unit. Issue 1 (13th May 2016) - Lamb, Lucy EM; Cox, AT; Fletcher, T; McCourt, AL
Abstract : This paper describes the development of the UK military's Ebola Virus Disease Treatment Unit (EVD TU) that was deployed to Sierra Leone as part of the UK response to the West African Ebola virus disease (EVD) epidemic in 2014 and 2015. It highlights specific challenges faced within this unique Field Hospital environment. The military EVD TU was initially established to provide confidence to international healthcare workers coming to Sierra Leone to assist in the international response to the EVD epidemic and formed a key part of the action plan by the UK's Department for International Development. It was designed and staffed to provide a high level of care to those admitted with suspected or confirmed EVD and was prepared to admit the first patient within 6 weeks of the original activation order by the Ministry of Defence. This article outlines the main hazards perceived at the outset of the operation and the methods used to mitigate the risk to the healthcare workers at the EVD TU. The article examines the mechanisms that enabled the hospital to respond positively to challenges that emerged during the deployment, while simultaneously reducing the risk to the healthcare workers involved in care delivery.